Artificial Force Induced Reaction (AFIR) Method for Exploring Quantum Chemical Potential Energy Surfaces. Issue 5 (3rd June 2016) - Maeda, Satoshi; Harabuchi, Yu; Takagi, Makito; Taketsugu, Tetsuya; Morokuma, Keiji
Abstract: In this account, a technical overview of the artificial force induced reaction (AFIR) method is presented. The AFIR method is one of the automated reaction‐path search methods developed by the authors, and has been applied extensively to a variety of chemical reactions, such as organocatalysis, organometallic catalysis, and photoreactions. There are two modes in the AFIR method, i.e., a multicomponent mode and a single‐component mode. The former has been applied to bimolecular and multicomponent reactions and the latter to unimolecular isomerization and dissociation reactions. Five numerical examples are presented for an Aldol reaction, a Claisen rearrangement, a Co‐catalyzed hydroformylation, a fullerene structure search, and a nonradiative decay path search in an electronically excited naphthalene molecule. Finally, possible applications of the AFIR method are discussed. Abstract : Finding reaction paths : the artificial force induced reaction (AFIR) method has been developed for exploring chemical structures and reaction pathways using computers. A technical overview of the AFIR method is presented, together with some numerical examples. The numerical results demonstrate its high applicability and efficiency